The Impact of Founder as brand on Customer Based Brand Equity: A case study on CAIA Cosmetics & Djerf Avenue - Östblom,Johanna; Thunholm,Filippa; Palklint,Klara (LBMG Strategic Brand Management - Masters Paper Series, 2025)
Purpose: This study aims to analyse how the founder as brand concept can affect Customer Based Brand Equity. The research aims to contribute insights on how founder representation can strengthen or weaken brand perception among consumers. Methodology: This research follows a quantitative, abductive design. Primary data were collected through a semi-structured focus group interview and secondary data were obtained from literature, articles and online platforms of the two Swedish founder-led case companies CAIA Cosmetics and Djerf Avenue. The analysis applies already existing theoretical models within Brand Management, and a self-developed 2×2 framework to explore how founder– brand alignment influences consumer perceptions. Findings: Founder as brand can boost early stages of brand equity such as awareness and imagery, but it leaves the later stages of judgements, feelings and loyalty more exposed if the founder’s image turns. Presented data showed CAIA’s broader set of brand assets, including product quality, clear visual codes and other credible voices increased trust when Bianca was less visible, while Djerf Avenue’s very close link between person and brand made negative news about Matilda spill over quickly and stick. Brands should leverage use founder as brand to build salience but simultaneously developing independent brand assets to preserve trust and loyalty. Research limitations: The research is a part of the Masters course Strategic Brand Management at Lund University, meaning some limits for the research regarding time and resources. The focus group consisted of a homogenous group of participants, and the new proposed 2x2 framework could therefore be tested in different industries, markets, target groups and cultural contexts to enhance validity. Originality/value: This study contributes by implementing a new 2x2 framework linking founder–brand alignment and brand independence to customer-based brand equity. The research provides new understanding based on case studies on two Swedish brands and combines insights from several existing theories combined with the new framework to reach new insights in a field where limited researchers have been made.
Keywords: Customer Based Brand Equity; Founder as brand; brand identity; CAIA Cosmetics; Djerf Avenue; Bianca Ingrosso; Matilda Djerf